Political violence in the form of 'Sara Suka' in Bauchi State, Nigeria. 1999-2013 - Ilelah, Kabiru Bello (2015)
The utilization of political violence in the form of thuggery (Sara Suka) has remained one of the quickest means of attaining and maintaining political power. The ‘Sara Suka’ is one of the major social problems defiling the peaceful co-existence of people in Bauchi state. The group is believed to be motivated and sponsored by politicians, in order for them to be used as a political catalyst of rigging and propaganda, intimidation and harassment, kidnapping and many other forms of social vices to the inclusion of even murder, thuggery, robbery, drug addiction, rape and theft. Hence, the return of democracy in 1999 or in the past democratic regimes any activity such as the ‘Sara Suka’ group is highly connected with violence. Since that period of the year 1999, the government and other experts have been in designing policies that can control or solve the problem of ‘Sara Suka’ in the state, but the situation continues to increase on a daily basis and there is high turnout of youth involvement in such act nowadays, despite these efforts made by the government. It is on the bases of these concerns that this study intends to explore the historical background of the ‘Sara Suka’ activities in Bauchi State. The study also examines the factors that influence youth involvement in the ‘Sara Suka’ activity. The study goes further to identify the major implication of ‘Sara Suka’ menace in the process of political development, as well as exploring some possible solution to the problem. Methodologically, the study uses a qualitative case study approach in understanding the ‘Sara Suka’ in the politics of Bauchi state. The two techniques of sampling were utilized, purposive for the ‘Sara Suka’ group of informants and snowballing which was used to identify the other three groups of the informants. Data were collected through one-on-one in depth interview with five ‘Sara Suka’ members, one retired member, two victims of the scenario and four others (expert, NGOs, vigilante, Districts head). The data were transcribed, coded and analyzed through inductive method. Subsequently, the result shows that the ‘Sara Suka’group emanated after the return of democracy in the year 1999, and their activities become worrisome in the 2003, and 2007 general elections in the state, and that the groups were created by politicians in order to win or maintain their political positions. The study reveals that there are political, social, and economic reasons behind the creation of the said group, so also the youth participation in the group. Moreover, the study understands that the implications of the ‘Sara Suka’ activity in the state include; the emergence of incompetent leaders, the emergence of the insurgency and small arms proliferation, political threat and the future of the youth and the state. Establishment of law and education, the eradication of poverty and the commitment of both the government and the society are the possible ways out to remedy the problem of the ‘Sara Suka’ in the state. Based on these findings, the study recommends that the people at the grass root level should organize themselves or creates a vigilante group who are equal to the task and at the same time ready to face any challenges that seek to impose havoc on their society and the state in general. The government should also make sure that the laws that were put in place to sanction or punish those that are involved in the ‘Sara Suka’, either the members or their sponsors, should be reviewed and enacted, so that anyone found guilty should be punished according to the law. Campaigns and elections should be conducted in a free and fair manner, if anyone is found using violence or any such tactic, should be penalized from contesting. The government should also ensure and provide adequate food, shelter, full security and safety to the people in order to bring back peace and harmony among the people of the state.